Kemandirian Petani dan Keberlanjutan Usahatani Padi Sawah Di Kecamatan Konda Kabupaten Konawe Selatan - Irianingsih Irianingsih; Bahari Bahari; Budiyanto Budiyanto (Universitas Halu Oleo, 2022)
The purpose of this study was to determine and analyze the independence of farmers, the sustainability of lowland rice farming, and the relationship between farmers' independence and the sustainability of lowland rice farming in Konda District, South Konawe Regency. Data sourced from lowland rice farmers in Konda District. The basis for consideration of making two villages the subject of this research is that the two villages are the villages with the highest number of lowland rice farmers in Konda District. The population of this research is 120 farmers of lowland rice in Cialam Jaya village and 80 farmers in Lawoila village. The research sample size was determined using the Slovin formula and the respondents were determined using cluster random sampling. Data analysis used descriptive analysis and Pearson correlation analysis. The results showed that the level of independence of farmers was included in the less independent category, which was 41.9 and the sustainability of farming was included in the less sustainable category, which was 37.0. The implication of the results of this study is that the independence of lowland rice farmers is one of the determining factors for the sustainability of lowland rice farming in Konda District in particular and South Konawe Regency in general.Keywords: farmer independence; sustainability of farming; rice paddy farming.